2011
DOI: 10.1371/journal.pone.0026803
|View full text |Cite
|
Sign up to set email alerts
|

Long Circulating Lectin Conjugated Paclitaxel Loaded Magnetic Nanoparticles: A New Theranostic Avenue for Leukemia Therapy

Abstract: Amongst all leukemias, Bcr-Abl positive chronic myelogenous leukemia (CML) confers resistance to native drug due to multi drug resistance and also resistance to p53 and fas ligand pathways. In the present study, we have investigated the efficacy of microtubule stabilizing paclitaxel loaded magnetic nanoparticles (pac-MNPs) to ascertain its cytotoxic effect on Bcr-Abl positive K562 cells. For active targeted therapy, pac-MNPs were functionalized with lectin glycoprotein which resulted in higher cellular uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…28 These results indicated that XNMs possessed a higher efficiency in drug delivery into A2780 cells than that of LNMs. Comparing the structures of polymers that formed LNMs and XNMs as well as their physicochemical characteristics, this cellular uptake enhancement might be attributed to the smaller particle size of XNMs.…”
Section: Cellular Uptake Studymentioning
confidence: 90%
See 1 more Smart Citation
“…28 These results indicated that XNMs possessed a higher efficiency in drug delivery into A2780 cells than that of LNMs. Comparing the structures of polymers that formed LNMs and XNMs as well as their physicochemical characteristics, this cellular uptake enhancement might be attributed to the smaller particle size of XNMs.…”
Section: Cellular Uptake Studymentioning
confidence: 90%
“…cellular uptake study Cellular uptake efficiency of coumarin 6-loaded nanomicelles (C6/XNMs and C6/LNMs) were conducted on A2780 cells using flow cytometry. 28 Typically, approximately 8,000 cells were seeded in each well of a 12-well plate and incubated overnight. The DMSO solution of coumarin 6 and coumarin 6-loaded nanomicelles was diluted in medium to get a concentration of 50 ng/ mL of coumarin 6.…”
Section: In Vitro Dtx Release From Dtx/xnmsmentioning
confidence: 99%
“…40 As such, lectins, such as wheat germ agglutinin (WGA), may be employed for targeting of NPs for cancer imaging or therapy. Despite the extensive applications of lectin-NP conjugates in investigating the glycan-NP interactions, 41 there is only a small number of studies using lectin-functionalized NPs for imaging applications.…”
Section: Common Targeting Ligands For Imaging Applicationsmentioning
confidence: 99%
“…In another study, paclitaxel-loaded magnetic nanoparticles (pac-MNPs) and lectin-conjugated pac-MNPs were found to have prolonged the circulation time in rat serum which indicated enhanced bioavailability and thus the therapeutic potential of paclitaxel. The treatment with the drug resulted in the arrest of the cells at G2-M phase and the paclitaxel-loaded nanoparticles mediated the cell death by activating the extrinsic and intrinsic pathways of apoptosis [77].…”
Section: Nanoparticlesmentioning
confidence: 99%